2019
DOI: 10.1103/physrevresearch.1.033140
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breaking in the body-fixed electron emission pattern due to electron-retroaction in the photodissociation of H2+ and D2+ close to threshold

Abstract: We present an experimental investigation of symmetry breaking of H 2 and D 2 molecules after single photoionization due to the Coulomb field of the emitted slow electron interacting with the parent cation during dissociation. The experiments were carried out by measuring the three-dimensional momentum vectors of the photoelectron and recoiling ion in coincidence using a reaction microscope. For photon energies close to threshold, the low-energy photoelectron influences the dissociation process, which results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…By changing σ from 10 to 50 gradually, the asymmetry parameters keep unchanged. The conclusion is different from the conclusions in [44][45][46][47], where the photoelectron energy is about 2 eV and thus the photoelectron may interact with another bound electron in a relatively long time. In this paper, the photoelectron energy is around 20 eV so that it quickly flies away and the effect of electron-electron repulsion on the final state can be neglected.…”
Section: Simulation Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…By changing σ from 10 to 50 gradually, the asymmetry parameters keep unchanged. The conclusion is different from the conclusions in [44][45][46][47], where the photoelectron energy is about 2 eV and thus the photoelectron may interact with another bound electron in a relatively long time. In this paper, the photoelectron energy is around 20 eV so that it quickly flies away and the effect of electron-electron repulsion on the final state can be neglected.…”
Section: Simulation Resultscontrasting
confidence: 80%
“…Serov and Kheifets [44] predicted that after single ionization of H 2 , the Coulomb interaction between the freed electron and the vibrating H + 2 may pump H + 2 from the 1sσ g state to the 2pσ u state, making the bound electron preferentially locate on the nucleus moving oppositely to the photoelectron. Later, Waitz et al [45] and Heck et al [46] experimentally observed this asymmetric distribution and confirmed such dynamics. Wang et al [47] used the reduced-dimensionality numerical model to simulate such a process and the simulation results can quantitatively explain the experimental measurement, ensuring the feasibility of such a reduced-dimensionality numerical model.…”
Section: Introductionmentioning
confidence: 75%
“…30,55 The nuclear dynamics of the ICD process can be described by propagating wave packets on the PECs of the initial and nal ICD states. In our calculations, we assume that the ionization step is instantaneous (sudden approximation), and we neglect the polarization caused by the slow photoelectron 56,57 and the interactions between the initial and nal ICD states similar to previous calculations of ICD dynamics. 58,59 Following these assumptions, the time evolution of the wave packets of the decaying and nal states can be described by the following set of time-dependent Schrödinger equations:…”
Section: Theorymentioning
confidence: 99%